Methodological Tools for Investment Risk Assessment for the Companies of Real Economy Sector - Zholonko, Tetiana; Grebinchuk, Olesia; Bielikova, Maryna; Kulynych, Yurii; Oviechkina, Olena (My University, 2021)
Methodological approaches to investing in companies and reducing the negative impact of risks that are formed at the macro and micro levels are considered in the article. The algorithm for expressing investment risks through related risks and conducting an investment risk assessment as a group process is defined. It has been determined that the defining features of investment risks are the environment, duration, and scope of the project, risk position, profile, risk appetite, consequences, capacity, and results of the impact on the investment project. An investment risk accounting system is formed, which is represented by a set of organized structural elements that perform functions related to planning and implementation of a set of measures that identify, assess, monitor, and control risks to minimize negative consequences and enhance opportunities. A method of forming a real portfolio of investment projects considering the dynamic risk factor has been developed.
Keywords: investment risks; investment project; risk assessment; risk-forming factors; chain process; system of equations; інвестиційні ризики; інвестиційний проект; оцінка ризику; ланцюговий процес; система рівнянь; кафедра фінансів